Menelisik Komunikasi Interpersonal dalam Mewujudkan Ketahanan Masyarakat Nelayan di Teluk Nibung Kota Tanjung Balai - Fitriani, Astri Rama; Hardiyanto, Sigit (Universitas Muhammdiyah Yogyakarta, 2026)
Based on the researcher's observations, the problems experienced by the fishing community in Gudang Haji Daham, Teluk Nibung are quite diverse, ranging from economic, educational and skills fields, especially how fishermen explore and contribute to building community resilience, as well as its impact on their socio-economic resilience. Based on these problems, the purpose of this study seeks to provide a concrete description of the interpersonal communication process that occurs in the fishing community of Teluk Nibung District to realize social and economic resilience amidst the challenges of coastal life. The method used in this study is descriptive qualitative to provide an overview of interpersonal communication of fishermen in realizing fishermen's resilience in Teluk Nibung, Tanjung Balai City. Data collection techniques used in the study were interviews structured by preparing a draft of questions that have been prepared, observation and documentation. Data analysis techniques used include data reduction, data presentation and drawing conclusions. Based on the results of the study, communication carried out by the fishing community in everyday conversations is an open interpersonal communication technique. Fishermen not only share information, but also show concern for each other by providing moral, financial, and labour assistance in difficult situations. The culture of mutual cooperation that they practice proves that interpersonal communication based on empathy can create closer relationships, not only as co-workers, but also as a family that looks after each other.